Quality evaluation model of Yemeni universities websites from students perspectives - Barraood, Samera Obaid Al-barak (2016)
Higher Education Institute (HEI) website is one of the platforms to promote academic programs as well as research, publication, and consultation activities; and so forth, that may contribute to the university achievements towards advancing its position in the local and international university ranking list. The website is also important in gaining the trust of stakeholders of the educational programs offered by the respective universities. Besides being able to efficiently provide required information to potential students, the HEI website should also ensure that the information can be accessed easily. The creation of such website is certainly not an easy task whereby some of the existing websites are not accessible due to its poor design. Thus, there is a need to design a high quality HEI website based on one of the quality standards such as the ISO 9126-1. This study aims to evaluate the quality of HEI websites in meeting the requirements of potential students. The evaluation focuses on the students’ perspectives of the observed HEI websites. A survey was conducted involving five established Yemeni universities websites. This study adopted the ISO 9126-1 software quality standard as the based theory. In addition, a few other related factors to content and requirements of HEI website were also taken into consideration. A HEI website evaluation model was constructed comprises of six quality factors: usability, content, web appearance, efficiency, functionality, and service quality. Based on the model, an online questionnaire was constructed for collecting data. The respondents of this study were 125 undergraduate and postgraduate students. The valid returned questionnaires were then analyzed using the SPSS software, PLS-SEM technique and WEBUSE analysis method. Even though, the hypothesis testing results showed that all hypotheses are acceptable, there were two quality factors that did not have significant effect on the HEI website quality: content and efficiency. In addition, the results revealed that the overall quality level of the HEI websites is good. However, some weaknesses in certain aspects were found, such as the searching function, design, content, and performance. This study also provides some suggestions for enhancing the website quality of the observed university websites